(3GdeYJeO aj GdCOhjI GdeaQOIs - (3GdeXaQ GdQShdj , jhSa Hf YeQ Hf Ydj Hf QShd GdJQceGfj, TeS GdOjf,J (B694 (3g` s ((3UdGM Hf OGhO Hf Ydi Hf OGZQ s)
(3ChdgG (B:s
(3hHYO (B: (3aEfi ENJUQJ gPG GdcJGH ef cJH cHGQ LeYJgG , LeYJ GdJWhjd hGdESgGH , hde CPcQ EdG GdehLhO Ohf eG jYSQ Ydi GdWdGH s
(3BNQgG (B:s
(3h gGgfG GfJgi GdZQV GdebUhO ef cJGH GdeYJeO GdeNJUQ ef cJGH LGeY GdCZPjI s
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B243 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B320s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B234 s
Keywords: (3GdWHs